2016
DOI: 10.1016/j.mjafi.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Median Canaliform Dystrophy of Heller occurring on thumb and great toe nails

Abstract: Median Canaliform Dystrophy of Heller is a rare but morphologically striking habit tic deformity of thumb nails characterized by midline longitudinal furrow with multiple transverse parallel lines. The proposed etiopathogenesis is repetitive trauma to the nail plate and cuticle, however some case reports have suggested familial occurrence and use of oral retinoids in its causation. Treatment is often prolonged and unsatisfactory, though some topical agents have been used successfully. We report a case of a you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 3 publications
0
19
0
2
Order By: Relevance
“…He was then prescribed topical 0.1% Tacrolimus ointment and Oral Fluoxetine at the dose of 50 mg daily. However, the case was lost to follow up after putting the patient first review [1]. Damevska et al reported 11 year old girl who developed canaliform dystrophy and long-term hypopigmentation following cryotheraphy of warts on proximal nail folds [6].…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…He was then prescribed topical 0.1% Tacrolimus ointment and Oral Fluoxetine at the dose of 50 mg daily. However, the case was lost to follow up after putting the patient first review [1]. Damevska et al reported 11 year old girl who developed canaliform dystrophy and long-term hypopigmentation following cryotheraphy of warts on proximal nail folds [6].…”
Section: Case Reportmentioning
confidence: 99%
“…Although the proposed etiopathogenesis is repetitive trauma in the form of pushing down the cuticle and proximal nail fold, in majority of cases the cause may be obscure. Some case reports have suggested familial occurrence and use of oral retinoids in its causation [1]. Histopathology classically shows parakeratosis, accumulation of melanin within and between the nail bed keratinocytes [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La dystrophie unguéale médiane, qu'on désigne aussi sous le nom de dystrophia unguis mediana canaliformis, dystrophie mé diane canaliforme ou solénonychie, est une affection de l'ongle peu courante qui touche les hommes et les femmes en proportions égales. Possiblement associée à un microtraumatisme de la matrice unguéale, l'affection est souvent symétrique et touche le plus souvent les pouces [1][2][3] . L'onychotillomanie, les tumeurs des ongles, le kyste mucoïde du doigt et la trachyonychie (ongles rugueux) sont d'autres diagnostics courants se manifestant par des défauts longitudinaux de l'ongle [4][5][6] .…”
unclassified
“…Bien que la dystrophie unguéale médiane puisse être traitée par l'application topique de corticostéroïdes, de tacrolimus et de tazarotène, il n'existe pas de preuves claires que les changements d'apparence de l'ongle disparaîtront [1][2][3] . Le patient a choisi de ne suivre aucun traitement, puisqu'il ne s'agissait que d'une question d'apparence.…”
unclassified